Communicating hydrocephalus associated with neurosarcoidosis diagnosed by endoscopic biopsy. Issue 2 (15th December 2019) - Maruno, Sayako; Naito, Tatsuhiko; Nakamoto, Fumiko Kusunoki; Kamisawa, Aya; Sato, Tatsuya; Seki, Tomonari; Maekawa, Risa; Hideyama, Takuto; Ushiku, Tetsuo; Shin, Masahiro; Shiio, Yasushi
Abstract: We present a case of communicating hydrocephalus associated with neurosarcoidosis in which the patient was diagnosed by endoscopic biopsy and successfully treated with corticosteroid therapy. The patient was a 53‐year‐old woman who presented with vertigo and nausea. Brain MRI revealed hydrocephalus and contrast‐enhancing areas only on the interthalamic adhesion. Sarcoidosis was suspected based on hilar lymphadenopathy and her past history of uveitis; however, there was no other organ involvement appropriate for biopsy. We performed endoscopic third ventriculocisternostomy and performed biopsy of nodular lesions of the interthalamic adhesion. Interestingly, endoscopy revealed numerous lesions on ventricular walls, which were not detected on contrast‐enhanced MRI. The histopathological examination revealed findings consistent with sarcoidosis. The patient was started on corticosteroid therapy, and her hydrocephalus improved conspicuously. Our case reinforces the notion that endoscopic biopsy is helpful in the definite diagnosis of neurosarcoidosis.